Water Service Delivery Issues and Challenges for the Urban Poor Zones in South Western Uganda - Muhamya, Horace; Ocan, Johnson; Adyanga, Akena Francis (East African Nature and Science Organization, 2024)
The article aims to examine the issues and challenges associated with providing water services to urban impoverished areas in South Western Uganda. The research methodology employed in this study involved conducting a comprehensive desktop study and literature review, systematically searching, and selecting peer-reviewed journal articles, books, and conference proceedings within a specified scope, using carefully chosen keywords and search criteria. After collating and evaluating the selected literature, a thorough synthesis was done to identify existing knowledge gaps and provide insights into the research questions under investigation. The main findings of the results highlight the need for integrated service models to expand water service delivery for the urban poor zones in southwestern Uganda. The study concludes that the problems addressed in this research and the suggestions presented provide the basis for improving water services to urban impoverished areas in South Western Uganda. This research will broaden service models for urban areas while also creating service models for locations with features of impoverished conditions. It is crucial to remember that households in urban cells were more likely to use improved water sources (including piped water on-premises), make regular payments for water, rely on shared sanitation facilities, and use manual sludge emptying services